NEW VIEWS ON THE ACTIVITY OF KHOJA AHROR VALI (American Journal of Interdisciplinary Research and Development, 2023)
In the article has been analyzed new views on the activity of Khoja Ahror Vali and studying the period of the Timurids, give a high assessment to the role and position of individual governors in the life of the country, and describe the activities of religious leaders and entire social groups one-sidedly. Besides, article has showed such a reaction to the activities of the Naqshbandiyya sect and its leaders was characteristic by historical sources.